Трансформації виробничих систем українських підприємств у 2022–2025 роках: уроки воєнного часу - Лоза, С.П. (Економічний вісник Донбасу, 2025)
У статті досліджено трансформацію виробничих систем українських підприємств у 2022–2025 роках в умовах воєнного стану. Обгрунтовано концептуальну модель, що включає сім напрямків адаптації: технологічну модернізацію, територіальну міграцію, реорганізацію ланцюгів постачання, фінансову стабілізацію, управлінську реструктуризацію, розвиток людського капіталу та інноваційну диверсифікацію. Виявлено синергетичний ефект комплексних стратегій адаптації, що забезпечили вищу операційну ефективність. Масштаби трансформацій перевершили всі попередні кризові періоди, створивши унікальні компетенції управління в умовах невизначеності. Воєнний досвід заклав основи для післявоєнної реконструкції та переходу до економіки знань, формуючи конкурентні переваги для майбутнього розвитку. This study examines the comprehensive transformations of production systems within Ukrainian enterprises during 2022–2025 under martial law conditions, analysing how businesses adapted to unprecedented wartime challenges. The research develops a conceptual model encompassing seven key transformation vectors: technological modernisation through accelerated digitalisation and resource planning systems integration; territorial migration with the formation of new industrial corridors in western and central regions; supply chain reorganisation emphasising localisation and diversification; financial stabilisation through state support programmes and international assistance; managerial restructuring with decentralised decision-making and scenario planning; human capital development through reskilling programmes and crisis management training; innovative diversification focussing on dual-use technologies. The scale and speed of these transformations exceeded all previous crisis periods in Ukrainian economic history, creating unique conditions for a natural experiment in studying the extreme limits of production system adaptation. The research demonstrates a powerful synergistic effect when enterprises simultaneously implemented multiple transformation strategies, achieving superior adaptability and operational efficiency compared to those pursuing isolated changes. These wartime transformations created unique competencies in uncertainty management, accelerated digital technology adoption, and crisis resilience that may become competitive advantages in international markets. The transformational experience laid fundamental foundations for Ukraine's future economic reconstruction and modernisation, creating prerequisites for transitioning from a traditional industrial model to a knowledge and high-technology economy. The findings provide strategic insights for post-war reconstruction policies and establish methodological foundations for developing crisis-resistant production systems.